Pelatihan Manajemen Risiko dalam Pengelolaan Koperasi Konsumen Wanita Mandiri Zayda Depok - Atmapratiwi, Heppy; Ridhowati, Ridhowati; Pangesti, Indah (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
Consumer cooperatives play an essential role in improving purchasing power and economic welfare by providing affordable goods and services for their members. However, their operations are exposed to various financial and non-financial risks that may hinder business continuity. At the Wanita Mandiri Zayda Consumer Cooperative in Depok, several critical issues were identified, including non-performing loans, unstable profit due to fluctuating product prices, low member participation, and insufficient managerial competence among staff and administrators. To address these challenges, structured and sustainable risk management practices are required. Therefore, a community service program titled “Risk Management Training in the Management of Wanita Mandiri Zayda Consumer Cooperative Depok” was implemented to enhance the capacity of cooperative administrators in identifying, analyzing, and mitigating risks. The program was delivered through interactive lectures, direct learning, group discussions, and participant evaluation. The results indicate improved understanding of risk management concepts and strategies, followed by participants’ commitment to applying mitigation measures in operational activities. This program is expected to serve as a concrete effort to strengthen governance quality and ensure the sustainability of women-based consumer cooperatives in Depok.